The portrayal of women: a corpus analysis of the representation around the word ‘wanita’ in the Malaysian Hansard Corpus - Anis Nadiah Che Abdul Rahman (Penerbit Universiti Kebangsaan Malaysia, 2024)
The term "women's issues" is often used too broadly, which can obscure the specific challenges women face. Understanding how parliamentarians categorize women's issues is crucial for grasping their perspectives from a political dimension. This allows politicians to shape discussions through their speeches, as their chosen words significantly influence how women's issues are framed and contextualized. This paper examines the Malaysian Hansard Corpus, a collection of parliamentary debates, to analyze how politicians conceptualize and present women as a political issue over a period of 61 years. Using corpus linguistics, this study investigates the representation of women through noun collocates of 'wanita' (woman). WordSmith Tool 7.0 and a Part of Speech tagger extracted a list of collocates with semantic content to analyze the semantic preferences associated with the term 'wanita' over time. The findings indicate that politicians semantically associate 'wanita' with categories related to national identity, attributes, conflict, culture, religion, public affairs, and quantification. Notably, discussions surrounding women's issues have become more favorable throughout parliamentary sessions. This research contributes to corpus linguistics by demonstrating how linguistic patterns can reveal shifts in political discourse over time. By systematizing these findings, the study provides a framework for understanding women's issues in Malaysian parliamentary debates through their semantic representations, illuminating how language use reflects evolving attitudes and priorities regarding women's rights and representation in political contexts.